Socioeconomic Characteristics of Households, Government Programs on Human Capital, and Natural Shocks as Determinants of Philippine Household Income Mobility - Monsura, Melcah Pascua (Archīum Ateneo, 2021)
The purpose of this study is to introduce income mobility analysis to examine households’ welfare through time. Income mobility in the Philippines has been characterized by offsetting forces of upward and downward mobility. In this kind of scenario, policy targeting for households’ welfare can be done by examining the drivers of income mobility. Pseudo-longitudinal panel data generated from the Family Income and Expenditures Survey (FIES), through the household matching method, were used to identify the households included in the study. The needed information on the levels of living and differences in income and expenditure of Filipino families were provided by FIES. In addition, the Becker, Kominers, Murphy, and Spenkuch (BKMS) framework was utilized to determine the factors that affect income mobility. Ordinary least squares (OLS) and multinomial logit regressions were used to explain and examine absolute and relative income mobility, respectively. The findings showed that households’ income mobility was influenced by geographical location, household heads’ marital status, educational attainment, and occupation. In addition, government investments in human capital development such as education, health, and social services were significant factors of income mobility. On the other hand, because of the country’s preparedness and planning before the onset of a natural disaster and immediate solutions in the aftermath of a disaster, natural shocks were found to be an insignificant factor of income mobility.